Analisis Hubungan antara Gaya Kepemimpinan, Motivasi, dan Kepuasan Kerja terhadap Turnover Intention - Azhari, Naeni (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
The relationship between leadership style, motivation and job satisfaction with employee turnover intention in today's work environment which is often characterized by dynamic change and high competition. Employees who feel dissatisfied with their jobs or are unmotivated may experience turnover intentions, which can have a negative impact on productivity and organizational stability. The main objective of this research is to understand the extent to which leadership style, motivation, and job satisfaction contribute to employee turnover intentions. This research method involves surveys and data analysis from employees at various levels in the organization. The research instruments used included questionnaires that measured employees' perceptions of their leadership style, motivation, job satisfaction, and turnover intentions. The data is then analyzed using statistical techniques such as regression to identify relationships between these variables. The research results show that there is a significant relationship between leadership style, motivation and job satisfaction with employee turnover intentions. These findings provide a deeper understanding of the factors that influence employee retention rates and provide a foundation for developing more effective management strategies in retaining key talent.